2022
DOI: 10.3389/fpubh.2022.991292
|View full text |Cite
|
Sign up to set email alerts
|

Effects of general and corona-specific stressors on mental burden during the SARS-CoV-2 pandemic in Germany

Abstract: The SARS-CoV-2 pandemic turned out to be a serious threat to mental and physical health. However, the relative contribution of corona-specific (DHs) and general stressors (DHg) on mental burden, and specific protective and risk factors for mental health are still not well understood. In a representative sample (N = 3,055) of the German adult population, mental health, potential risk, and protective factors as well as DHs and DHg exposure were assessed online during the SARS-CoV-2 pandemic (June and July 2020).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 82 publications
0
0
0
Order By: Relevance
“…However, psychological adaptation to the pandemic and willingness to comply with the restricting measures do not merely depend on external factors [16][17][18]: For example, studies demonstrated that openness and extraversion acted as resilience factors [1,2,19,20] whereas neuroticism could be seen as a vulnerability factor for experiencing emotional distress during the pandemic [3,[21][22][23][24][25][26]. Targeting the important question of protective factors in these challenging times [27,28], further studies have found that defense mechanisms [21,[29][30][31], coping strategies, and resilience [32][33][34][35][36][37][38] were significantly related to distress during the pandemic. Regarding behavioral aspects such as compliance with the rules of social distancing, studies have focused on how different reactions and attitudes are related to egocentric, unempathetic, and antisocial traits, but come to dissenting conclusions [39][40][41][42].…”
Section: Introductionmentioning
confidence: 99%
“…However, psychological adaptation to the pandemic and willingness to comply with the restricting measures do not merely depend on external factors [16][17][18]: For example, studies demonstrated that openness and extraversion acted as resilience factors [1,2,19,20] whereas neuroticism could be seen as a vulnerability factor for experiencing emotional distress during the pandemic [3,[21][22][23][24][25][26]. Targeting the important question of protective factors in these challenging times [27,28], further studies have found that defense mechanisms [21,[29][30][31], coping strategies, and resilience [32][33][34][35][36][37][38] were significantly related to distress during the pandemic. Regarding behavioral aspects such as compliance with the rules of social distancing, studies have focused on how different reactions and attitudes are related to egocentric, unempathetic, and antisocial traits, but come to dissenting conclusions [39][40][41][42].…”
Section: Introductionmentioning
confidence: 99%